1998
DOI: 10.1016/s1044-0305(98)00178-0
|View full text |Cite
|
Sign up to set email alerts
|

Structure and fragmentation mechanisms of isomeric T-rich oligodeoxynucleotides: A comparison of four tandem mass spectrometric methods

Abstract: Understanding the product-ion spectra of T-rich tetradeoxynucleotides is a starting point in the development of a mass spectrometric scheme to determine the mutagenicity of individual types of DNA damage. We obtained product-ion spectra for electrospray-produced ions that were activated in the ion source (electrospray ionization-source collision-activated-dissociation) and by high-energy collisions in the MS/MS mode of a four-sector instrument. We also activated singly and doubly charged ions by low-energy col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
86
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 31 publications
11
86
4
Order By: Relevance
“…All oligonucleotides were found to have substantial loss of labile nucleobase, i.e., adenine, to form abundance [M-AH] ϩ . In contrast to the previous studies using smaller oligonucleotides [22,23] loss of thymine was not found. Apart from the [M-AH] ϩ ions, series of [a n -AH] ϩ and w n ϩ ions were observed, where n is an even number.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…All oligonucleotides were found to have substantial loss of labile nucleobase, i.e., adenine, to form abundance [M-AH] ϩ . In contrast to the previous studies using smaller oligonucleotides [22,23] loss of thymine was not found. Apart from the [M-AH] ϩ ions, series of [a n -AH] ϩ and w n ϩ ions were observed, where n is an even number.…”
Section: Resultscontrasting
confidence: 99%
“…These internal ions have previously been observed in the study of the prompt dissociation of some oligonucleotides under IR-MALDI conditions, i.e., the so-called Z*-ions [17]. Since these double cleavages occur at a distance from each other, charge-remote mechanism [22] is believed to play a significant role in the backbone cleavage.…”
Section: Metastable Dissociationmentioning
confidence: 85%
“…Secondary dissociation of these ions produced an array of backbone cleavage products ("sequence ions") labeled w n and a n -B according to the McLuckey nomenclature [32]. The general mechanism shown in Scheme 1 has been proposed to explain the formation of these kinds of fragments [33,34]. The assortment of sequence ions visible in Figure 2a indicates that cleavage has occurred at nearly every interresidue junction along the phosphate backbone, as indicated by the series of slash marks overlaid on the sequence shown in Figure 2a.…”
Section: Fragmentation Of Low Charge State Precursorsmentioning
confidence: 99%
“…The observed base loss preference was AϷGϾCϾϾT. Gross and coworkers proposed an intramolecular proton transfer from the 5Јphospate to the base resulting in a zwitterionic intermediate from which a neutral base is lost and subsequent cleavage leads to formation of the a n -B and w n ions [26,28,29]. Under ESI and source CAD conditions, Gross and coworkers observed that the ease of formation of a n -B fragment ions is GϾCϷAϾϾT.…”
Section: Fragmentation Mechanisms Proposed In the Literaturementioning
confidence: 99%